Penilaian Baku Mutu Beberapa Parameter Baku Mutu Terpilih untuk Penilaian Kerusakan Tanah - Resti Aulia; Muhammad Syarbini; Ratna Ratna (Acta Solum, 2023)
The negative impact of open pit mining is damage to the environment. Damage to forest ecosystems results in decreased environmental quality, especially in soil as a biomass producer. The solution to the impacts caused by open pit mining is planning from the initial to post-mining stages prior to mining as an effort to preserve the environment. This study aims to determine the value and distribution of soil damage on selected parameters in the post-mining reclamation area. The research was conducted using a descriptive exploratory method with data obtained based on the analysis of the physical and chemical properties of the soil on selected parameters in the laboratory as primary and secondary data. Soil damage status in block 2 jackfruit pit in the post-mining reclamation area of ​​CV. Cinta Puri Pratama, Mataraman District, Banjar Regency, South Kalimantan is classified as slightly damaged with the limiting factor being bulk density, based on the results of the assessment of the quality standards of several selected parameters for soil damage referring to Government Regulation Number 150 of 2000 concerning controlling soil damage for biomass production that there is damage to post-mining reclamation land the existence of the parameters studied shows a value that exceeds the critical threshold as evidenced through the results of an evaluation of the damage status of post-mining reclamation land, if even one of the parameter thresholds is exceeded, the soil is declared damaged, while the evaluation results show that there is one parameter that has exceeded the critical threshold.